Sovereign Bond Contracts: Flaws in the Public Data?. Issue 2 (2nd October 2018) - Kropp, Andrea E; Weidemaier, W Mark C; Gulati, Mitu
Abstract: Commercial databases now make available to paying clients information about the legal terms in sovereign loan contracts. This information is important to academic researchers, to policy institutions such as the International Monetary Fund, and to investors and other market actors. For a random sample of 10 countries, the authors compare this data to a hand-coded sample of bond terms. They find significant error rates in the commercial databases, which vary significantly by country and by the legal term at issue. In some cases, they document error rates well over 75 per cent. They also describe important limitations in the data, especially the use of binary coding schemes that obscure important differences in the rights conferred by different sovereign loan contracts.